Analisis Strata Norma Roman Ingarden dalam Antologi Puisi Ayat-ayat Api Karya Sapardi Djoko Damono - Lestari Mahanani; Sudirman Shomary (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
The importance of the beauty of poetry and the clarity of the meaning of poetry is the background in this research. Through the study of the Strata Norm Roman Ingarden, it is hoped that the beauty of poetry and the clarity of meaning is reflected in the layers of sound, layers of meaning and layers of objects. The problems in this research are: How is the analysis of the Strata Norms of Roman Ingarden in the Anthology of the Poetry of the Fire Verses by Sapardi Djoko Damono? This research uses a descriptive method. Data collection techniques using hermeneutic techniques and analyzed by content analysis techniques (content analysis). The results of this study can be concluded that there is a normative stratum of Roman Ingarden in the poetry anthology of Ayat-ayat Api by Sapardi Djoko Damono in the form of layers of sound including vowel repetition (assonance) and consonant repetition (alliteration). Then there are layers of meaning in the form of lexical meaning and grammatical meaning. Furthermore, there is an object layer containing the actors, the setting of the place, the setting of time and the objects presented in the poem.